Institutional Capacity Building dalam Mendukung Kebijakan Nasional Anti Narkoba pada Badan Narkotika Nasional Kabupaten Blitar - Wydha Mustika Maharani; Leny Mastora; Dhiptya Ratri Anggraheni (Badan Riset dan Inovasi Daerah Kota Surakarta, 2026)
The gap between the broad mandate of national anti-drug policy and the limited institutional capacity at the local level remained a major challenge in public governance. This study aimed to analyse the institutional capacity development of the National Narcotics Agency of Blitar Regency in supporting the implementation of national anti-drug policy. A qualitative approach with a case study design was employed. Data were collected through semi-structured interviews with seven informants, field observation, and document analysis. Using Grindle’s capacity building framework, the findings showed that the institutional capacity of the National Narcotics Agency of Blitar Regency had been developed through a combination of personnel development, teamwork culture, digital public communication, and cross-sector collaboration. However, this capacity remained compensatory, as it was used to address structural limitations, including personnel shortages, unequal access to technical training, limited operational facilities, weak local budgetary support, and the absence of strong local regulations. The study argued that the effectiveness of national anti-drug policy at the regency level did not depend solely on legal mandates, but also on local institutional capacity supported by adequate financing, operational regulations, and more institutionalised cross-sector networks.